2021
DOI: 10.3389/fnagi.2021.774477
|View full text |Cite
|
Sign up to set email alerts
|

Alleviative Effect of Alpha-Lipoic Acid on Cognitive Impairment in High-Fat Diet and Streptozotocin-Induced Type 2 Diabetic Rats

Abstract: Background: The intricate relationship between type 2 diabetes mellitus (T2DM) and Alzheimer’s disease (AD) suggests that insulin is involved in modulating AD-related proteins. Alpha-lipoic acid (ALA) can improve insulin resistance (IR) in diabetic rats. However, the role of ALA in alleviating the cognitive decline of T2DM is not yet clear. This study examined the ameliorative effect of ALA on cognitive impairment, cerebral IR, and synaptic plasticity abnormalities in high-fat diet (HFD) plus streptozotocin (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…Further research is required; however, as we show here, ALA improves the glutathione system in both analyzed brain structures of HFD-fed rats. Recent studies also confirm that ALA improves cognitive function by normalizing brain glucose metabolism and the expression of synaptic plasticity proteins [ 53 , 112 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Further research is required; however, as we show here, ALA improves the glutathione system in both analyzed brain structures of HFD-fed rats. Recent studies also confirm that ALA improves cognitive function by normalizing brain glucose metabolism and the expression of synaptic plasticity proteins [ 53 , 112 ].…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies indicate that ALA improves cognitive function in insulin-resistant rats. ALA normalizes insulin signaling, brain glucose metabolism, and synaptic plasticity in the cerebral cortex and hippocampus of diabetic rats [ 53 ]. However, little is known about the effects of ALA on brain redox homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…ALA enhanced the protein expression of PI3K/AKT in the soleus muscle and reduced IR in rats with T2DM in the present study. Our previous study also found that ALA enhanced PI3K/AKT protein expression in the liver and brain tissues of rats with T2DM (Ko, Lo, et al, 2021; Ko, Xu, et al, 2021). ALA increases IRS‐1 protein expression in muscles and increases the binding of IRS‐1 to regulatory subunit p85 of PI3K in obese Zucker rats (Shay et al, 2009).…”
Section: Discussionmentioning
confidence: 60%
“…In this model, the lipoic acid intervention was associated with increased GLUT1 expression in the hippocampus and improved cognitive function and memory [ 194 ]. In a high-fat-fed STZ induced rat model of T2D, the 13-week lipoic acid intervention increased the expression of IRS1, PI3K, the pAKT/AKT ratio and the pGSK3β/GSK3β ratio in the hippocampus and promoted increased levels of IDE and improved cognitive function compared to the untreated diabetic mouse model [ 195 ]. In humans, a placebo-controlled clinical trial investigated the effectiveness of differing oral lipoic acid doses in T2D participants, and lipoic acid was associated with an enhanced metabolic clearance rate (MCR) of glucose, indicating increased insulin sensitivity.…”
Section: Is There Potential In Evaluating Insulin Mimetics For Ad Tre...mentioning
confidence: 99%